Dialect Features of the Siberian Tatars Song Culture - KARKINA, S.V; NURGAYANOVA, N.K; KAUR, M (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The object of the research is the traditional song culture of the Tatar population of Siberia in the context of dialect features. The article analyses song samples obtained during expeditions to the Novosibirsk and Tyumen regions, where Tatars live. As a result of the research, various and interesting, the material was recorded. Information was collected on the basis of a questionnaire to collect song folklore for a detailed analysis of the recorded sample, which allowed further identification of the distribution area and local dialect features, as well as modern forms of traditional song creation among the Tatar population of Siberia. RESUMEN El objeto del trabajo de investigación es la cultura tradicional de la canción de la población tártara de Siberia en el contexto de las características del dialecto. El artículo analiza muestras de canciones obtenidas durante expediciones a las regiones de Novosibirsk y Tyumen, donde viven los tártaros. Como resultado de la investigación, se grabó material variado e interesante. La información se recopiló sobre la base de un cuestionario para recopilar el folklore de la canción para un análisis detallado de la muestra grabada, lo que permitió una mayor identificación del área de distribución y las características del dialecto local, así como formas modernas de creación de canciones tradicionales entre la población tártara de Siberia.